Виборчий процес в умовах формування моделі паритетної демократії : основоположні принципи. - Кормич, Л.І.; Кормич, Л.И.; Kormich, L. (My University, 2012)
The present article provides the analyses of the essence and principles of the parity democracy. The main features of forms and methods of different levels elections campaigns under such a model are also characterized. The dynamics of institutional, legal, ideological transformations of society on the way to parity democracy are shown.
Кормич Л.І. Виборчий процес в умовах формування моделі паритетної демократії : основоположні принципи. / Л.І.Кормич // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса, 2012. – Вип. 47. – С. 20 - 27.
Keywords: Сутність і принципи паритетної демократії; Паритетна демократія; Виборчий процес; Принцип паритетності в Україні; Принцип паритетности в Украине; Избирательный процесс; Паритетная демократия; Сущность и принцыпы паритетной демократии; SUMMARY OF PRINCIPLE and parity democracy; parity democracy; The electoral process; The principle of parity in Ukraine